Comparison of Verbal and Physical Bullying Incidence among Elementary Students in Jayapura - Rispah Purba; Mona Safitri Fatiah; Afwan Syarif (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Bullying has increasingly affected elementary school students, with prevalence estimated at 25%. However, there is a lack of definitive data comparing bullying incidents between public and private elementary schools. This study aimed to compare the incidence of verbal and physical bullying among students at two elementary schools in Jayapura. A cross-sectional design was used, conducted in July 2024. The study involved a total population of 987 students, with a purposive sample of 102 students each from Inpres II Waena State Elementary School (public) and Muhammadiyah Elementary School (private). Data were collected via questionnaires and analyzed using Stata 14, applying bivariate analyses with chi-square tests. Findings revealed that verbal bullying was more prevalent at Inpres II Waena State Elementary School (66.7%) compared to Muhammadiyah Elementary School. Key factors associated with bullying included gender, age at first experience of bullying, and the availability of complaint channels. Verbal bullying often manifests as teasing or jokes, which are normalized due to the absence of firm sanctions for perpetrators. These results highlight the need for stronger school policies and structured reporting systems to address verbal bullying in both public and private school settings. Keywords: incidence of bullying, students, elementary school, counseling